Hypoxia-Inducible Factor-1 Alpha Expression Correlates with Lymphovascular Invasion and Nodal Metastasis in Invasive Breast Cancer - Christinahadi, Agnes Dyah; Nelwan, Berti Julian; Cangara, Muhammad Husni; Miskad, Upik Anderiani; Tawali, Suryani; Arsyadi, Gunawan (Asian Pacific Journal of Cancer Biology, 2026)
Background: Breast cancer prognosis is critically influenced by lymphovascular invasion (LVI) and lymph node metastasis. Hypoxia-inducible factor-1 alpha (HIF-1α) is a key protein implicated in tumor progression and metastasis. This study aimed to investigate the relationship between HIF-1α expression and the presence of LVI and regional lymph node metastasis in invasive breast cancer. Methods: This cross-sectional study analyzed 80 paraffin-embedded tissue specimens from participants with stage I–III invasive breast carcinoma. Participants were categorized based on the presence or absence of LVI and lymph node metastasis. HIF-1α expression was evaluated using immunohistochemistry and a semi-quantitative scoring system (IR-Score). The association between HIF-1α expression (positive vs. negative) and clinicopathological variables was analyzed using the Chi-Square test and odds ratio (OR) calculations. Results: Positive HIF-1α expression was predominant in tumors with LVI (74.1 %) or lymph node metastasis (70.3 %). A significant association was found between HIF-1α expression and LVI (p=0.012), with HIF-1α-positive tumors showing an approximate four-fold increased risk for LVI (OR 3.896; 95 % CI 1.451–10.462) compared to HIF-1α-negative samples. Similarly, a significant association was observed between HIF-1α expression and lymph node metastasis (p=0.031), conferring an increased risk when compared to HIF-1α-negative tumors (OR 3.947; 95 % CI 1.256–12.409). The mean proportion of stained cells was significantly higher in LVI-positive tumors (p=0.015) and metastatic tumors (p=0.039). Conclusion: HIF-1α expression is significantly associated with lymphovascular invasion and lymph node metastasis in invasive breast cancer. These findings underscore the potential of HIF-1α as a prognostic biomarker for tumors with high metastatic potential.